2015
DOI: 10.1002/smll.201502106
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilic Nitrogen and Sulfur Co‐doped Molybdenum Carbide Nanosheets for Electrochemical Hydrogen Evolution

Abstract: Nitrogen and sulfur dual-doped Mo2 C nanosheets provide low operating potential (-86 mV for driving 10 mA cm(-2) of current density). Co-doping of N and S heteroatoms can improve the wetting property of the Mo2C electrocatalyst in aqueous solution and induce synergistic effects via σ-donation and π-back donation with hydronium cation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
122
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(122 citation statements)
references
References 31 publications
0
122
0
Order By: Relevance
“…[36] However, further, it was demonstrated that the intrinsic HER activity of Mo 2 C is usually limited by their large density of empty d-orbitals on the Mo, which restricts the desorption of adsorbed H (H ads ) to generate H 2 . [43] However, nitrogen-doping (N-doping) often intermixes into carbon matrix rather than intercalating into Mo 2 C active sites, [16,[44][45][46][47][48] and thus how to construct a controllable N-doping into Mo 2 C activation site still remains a great challenge. [43] However, nitrogen-doping (N-doping) often intermixes into carbon matrix rather than intercalating into Mo 2 C active sites, [16,[44][45][46][47][48] and thus how to construct a controllable N-doping into Mo 2 C activation site still remains a great challenge.…”
Section: Introductionmentioning
confidence: 99%
“…[36] However, further, it was demonstrated that the intrinsic HER activity of Mo 2 C is usually limited by their large density of empty d-orbitals on the Mo, which restricts the desorption of adsorbed H (H ads ) to generate H 2 . [43] However, nitrogen-doping (N-doping) often intermixes into carbon matrix rather than intercalating into Mo 2 C active sites, [16,[44][45][46][47][48] and thus how to construct a controllable N-doping into Mo 2 C activation site still remains a great challenge. [43] However, nitrogen-doping (N-doping) often intermixes into carbon matrix rather than intercalating into Mo 2 C active sites, [16,[44][45][46][47][48] and thus how to construct a controllable N-doping into Mo 2 C activation site still remains a great challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the fascinating physicochemical and electronic properties arising from the small dimensions and quantum confinement effects (QCE) [1][2][3], ultrathin nanosheets have been the focus of substantial research in the light of fundamental studies and their broad applications in various fields, including optoelectronic devices [4], energy conversion and storage [5], sensors [6][7][8][9], biomedicine [10], and catalysis [11][12][13][14][15]. In particular, polymeric graphitic carbon nitride nanosheets (GCNNs), an n-type semiconductor, have been receiving considerable attention due to their many intriguing advantages such as the fact that they contain no metal, and nontoxicity, easy availability, sensitive photo-response, excellent chemical and thermal stability, and unique electronic structures [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…[1] Theoxygen evolution reaction (OER) and hydrogen evolution reaction (HER) are two important half reactions involved in electrochemical water splitting. [14] In the studies of the OER or HER processes,L ie tal. [3] Therefore,t he development of alternative non-noble metal catalysts with low-cost and earth abundance has become ag reat challenge for the HER or OER.…”
mentioning
confidence: 99%
“…[12] Owing to their special simple metallic structures with small carbon atoms in the interstitial voids of the densely packed host lattice,TMCs are endowed with the interstitial alloy properties and have attracted considerable attention in catalytic and electrochemical fields. [14] In the studies of the OER or HER processes,L ie tal. [14] In the studies of the OER or HER processes,L ie tal.…”
mentioning
confidence: 99%